Blame framing and prior knowledge influence moral judgments for people involved in the Tulsa Race Massacre among a combined Oklahoma and UK sample - Durham, Justin D.; Rosen, Adon F. G.; Gronlund, Scott D. (Frontiers in Psychology, 2024)
Introduction: How an event is framed impacts how people judge the morality of those involved, but 12 prior knowledge can influence information processing about an event, which also can impact moral 13 judgments. The current study explored how blame framing and self-reported prior knowledge of a 14 historical act of racial violence, labeled as Riot, Massacre, or Event, impacted individual’s 15 cumulative moral judgments regarding the groups involved in the Tulsa Race Massacre (Black 16 Tulsans, the Tulsa Police, and White Tulsans). 17 Methods and results: This study was collected in two cohorts including undergraduates attending 18 the University of Oklahoma and individuals living in the United Kingdom. Participants were 19 randomly assigned to a blame framing condition, read a factual summary of what happened in 20 Tulsa in 1921, and then responded to various moral judgment items about each group. Individuals 21 without prior knowledge had higher average Likert ratings (more blame) towards Black Tulsans and 22 lower average Likert ratings (less blame) towards White Tulsans and the Tulsa Police compared to 23 participants with prior knowledge. This finding was largest when what participants read was framed 24 as a Massacre rather than a Riot or Event. We also found participants with prior knowledge 25 significantly differed in how they made moral judgments across target groups; those with prior 26 knowledge had lower average Likert ratings (less blame) for Black Tulsans and higher average Likert 27 ratings (more blame) for White Tulsans on items pertaining to causal responsibility, intentionality, 28 and punishment compared to participants without prior knowledge. 29 Discussion: Findings suggest that the effect of blame framing on moral judgments is dependent on 30 prior knowledge. Implications for how people interpret both historical and new events involving 31 harmful consequences are discussed.